The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21037/gs.2017.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Combined associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) followed by left trisectionectomy and Whipple operation for PNET

Abstract: Pancreatic neuroendocrine tumor (PNET) is slow-growing, and account only for 2% of all pancreatic primary tumors. Surgical resection is still the only curative treatment for PNET patients. Unfortunately, most of PNETs was found with unresectable multiple liver metastases and extrahepatic metastasis as their characteristics of non-functional and asymptomatic. With advances in liver surgery in these years, especially combined associating liver partition and portal vein ligation for staged hepatectomy (ALPPS), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(22 reference statements)
1
1
0
2
Order By: Relevance
“…15 Ji et al has reported a case of a patient with a pancreatic NEN and multiple liver metastases in whom ALPPS followed by left trisectionectomy and Whipple procedure has been performed. 30 In the present study, which to the best of our knowledge is the first report on ALPPS in a case series of patients with unresectable NE LM, the 1-and 2-year DFS and OS were 73.2%, and 41.8% and 95.2% and 95.2%, respectively. The median DFS was 17.7 months.…”
Section: Discussionsupporting
confidence: 46%
“…15 Ji et al has reported a case of a patient with a pancreatic NEN and multiple liver metastases in whom ALPPS followed by left trisectionectomy and Whipple procedure has been performed. 30 In the present study, which to the best of our knowledge is the first report on ALPPS in a case series of patients with unresectable NE LM, the 1-and 2-year DFS and OS were 73.2%, and 41.8% and 95.2% and 95.2%, respectively. The median DFS was 17.7 months.…”
Section: Discussionsupporting
confidence: 46%
“…Forty-one patients with NET requiring the ALPPS approach have been published so far (http://fp.amegroups. cn/cms/ef5b8bf3a11b76b474fa9762e46828a7/hbsn-20-355-3.docx) (22,27,28,(32)(33)(34)(35)(36)(37)(38)(39). In all the patients but one, the treatment was done for hepatic NET metastases.…”
Section: Alpps Cases In Net Patientsmentioning
confidence: 99%
“…Клас сический вариант ALPPS заключается в перевязке правой ветви воротной вены с рассечением паренхимы и последующим выполнением правосторонней или расширенной правосторонней гемигепатэктомии [12][13][14]. В то же время при обширном поражении левой доли возможно выпол нение перевязки левой воротной ветви с пересечением паренхимы и выполнением расширенной левосторонней гемигепатэктомиитак называемый "обратный" ALPPS [15]. Приводим клиническое наблюдение.…”
Section: вве де ниеunclassified
“…В мире выполнено более 1000 ALPPS, из них лишь 14% -при ГЦК [23,24]. В литературе описано 6 наблюдений обратного ALPPS, большая часть из которых выполнена при метастазах колоректального рака (таблица) [15,[24][25][26][27]. Описано 1 наблюдение, в котором эта операция была выполнена лапароскопически [28].…”
Section: вве де ниеunclassified